Confirmatory factor analysis of digital skills on the use of mobile banking services in Subang district - Arsylia, Lulu; Giri, Refi Rifaldi Windya (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
The research aimed to identify and validate the digital skills required to use mobile banking services in Subang Regency. The study used non-probability and purposive sampling techniques to survey 350 banking customers who use mobile banking services in the Subang Regency. The results of the digital skills factor analysis showed that the indicators of each latent variable, including operational mobile skills, information navigation skills, social skills, and creative skills, were valid and able to represent their respective constructs. However, the model fit value did not meet the criteria, indicating that modifications were necessary to obtain a fit model. This study provides a starting point for further research to explore the model using the Exploratory Factor Analysis (EFA) analysis method or make modifications using the Confirmatory Factor Analysis (CFA) method to obtain a fit model that can contribute as a medium to confirm relevant and valid factors representing their constructs